2018
DOI: 10.1021/acschembio.8b00438
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Suggests a New Role for Ceramide Synthase in Phagocytosis

Abstract: Phagocytosis is an evolutionarily conserved biological process where pathogens or cellular debris are cleared by engulfing them in a membrane-enclosed cellular compartment called the phagosome. The formation, maturation, and subsequent degradation of a phagosome is an important immune response essential for protection against many pathogens. Yet, the global lipid profile of phagosomes remains unknown, especially as a function of their maturation in immune cells. Here, we show using mass spectrometry based quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 33 publications
4
68
0
Order By: Relevance
“…It is important to stress that the use of mass spectrometry as a platform to examine phagosomes carries the potential to fill important gaps in the field. While the phagosomal proteome has been widely investigated, other phagosomal 'omics' such as the lipidome and glycome have been studied to a significantly lesser extent [57,58]. Because of the increasingly recognized contribution of lipids, carbohydrates and metabolites to phagosomal dynamics, defining changes in their molecular landscapes in phagosomes, will likely render important advances in the field, especially in the understanding of host-pathogen interactions [59].…”
Section: Proteomicsmentioning
confidence: 99%
“…It is important to stress that the use of mass spectrometry as a platform to examine phagosomes carries the potential to fill important gaps in the field. While the phagosomal proteome has been widely investigated, other phagosomal 'omics' such as the lipidome and glycome have been studied to a significantly lesser extent [57,58]. Because of the increasingly recognized contribution of lipids, carbohydrates and metabolites to phagosomal dynamics, defining changes in their molecular landscapes in phagosomes, will likely render important advances in the field, especially in the understanding of host-pathogen interactions [59].…”
Section: Proteomicsmentioning
confidence: 99%
“…Law et al 27 found that VLC Cer were toxic and induced mithophagy in cardiomyocytes. Studies on phagocytes 28 revealed that VLC Cer could be essential for phagosome maturation in immune cells. VLC sphingolipids were found to be crucial in the survival of invariant natural killer T cells in thymus and liver 29 .…”
mentioning
confidence: 99%
“…To confirm whether feeding of paraquat and loss of SOD1 function led to an increase in ROS levels in the larval brain, we measured the levels of oxidized phospholipids, using quantitative mass spectrometry (MS)-based lipidomics (Kamat et al, 2015; Kory et al, 2017; Pathak et al, 2018; Tyurina et al, 2000). On feeding C155-GAL4/+ larvae with 5 mM paraquat, we enriched and detected nine oxidized polyunsaturated fatty acids (PUFAs), belonging to the phosphatidylserine (PS) and phosphatidylethanolamine (PE) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All the phospholipid species analysed in this study were quantified using the multiple reaction monitoring (MRM) high-resolution scanning method on a Sciex X500R QTOF LC-MS with an Exion-LC series quaternary pump. All data were acquired and analysed using SciexOS software as described before (Pathak et al, 2018). LC separation was achieved using a Gemini 5U C-18 column (Phenomenex, 5 μm, 50×4.6 mm) coupled to a Gemini guard column (Phenomenex, 4×3 mm, Phenomenex security cartridge).…”
Section: Methodsmentioning
confidence: 99%